2016
DOI: 10.3386/w22636
|View full text |Cite
|
Sign up to set email alerts
|

Trade and the Environment: New Methods, Measurements, and Results

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 28 publications
3
63
0
Order By: Relevance
“…Production strategies at the micro level and their impact on emissions complete the picture of the impact of trade on emissions at the global level. From our perspective, and in line with (Cherniwchan et al, 2017), the pollution offshoring hypothesis is particularly interesting. Although similar to the PHH, according to (Cherniwchan et al, 2017) [p. 4] it 'explicitly links firm level decisions to offshore dirty intermediate inputs to trade liberalization'.…”
Section: Global Structural Change Trade and The Pollution Haven Hyposupporting
confidence: 72%
See 1 more Smart Citation
“…Production strategies at the micro level and their impact on emissions complete the picture of the impact of trade on emissions at the global level. From our perspective, and in line with (Cherniwchan et al, 2017), the pollution offshoring hypothesis is particularly interesting. Although similar to the PHH, according to (Cherniwchan et al, 2017) [p. 4] it 'explicitly links firm level decisions to offshore dirty intermediate inputs to trade liberalization'.…”
Section: Global Structural Change Trade and The Pollution Haven Hyposupporting
confidence: 72%
“…More recently, Aichele and Felbermayr (2015) empirically assessed the post-Kyoto protocol effects in terms of emissions trading and found that the binding commitments under Kyoto have increased committed countries' embodied carbon imports from non-committed countries, by around 8% and increased the emissions intensity of their imports by about 3%. (Cherniwchan et al, 2017) provides a recent review of the methods, findings and policy implications for trade and the environment, which points to the importance of micro-level analyses for empirical assessment of the PHH. The authors combine reviews of traditional decomposition analyses with a partial equilibrium model of firms (and plants) strategic decisions.…”
Section: Global Structural Change Trade and The Pollution Haven Hypomentioning
confidence: 99%
“…The relationship between trade and environmental outcomes has been the focus of a large literature for some time (see for instance Antweiler et al, ; Cherniwchan et al, ; Cole & Elliott, ; Copeland & Taylor, ; Halicioglu & Ketenci, ; Levinson & Taylor, ). While most of the initial research was based on interindustry trade, there has been an increasing trend in research on intra‐industry trade, recognizing the vast volume of trade that happens within industries (see Aralas & Hoehn, ; Benarroch & Weder, ; Cole & Elliott, ; Fung & Maechler, ; Gürtzgen & Rauscher, ; Haupt, ; Levy & Dinopoulos, ; Roy, among others).…”
Section: Introductionmentioning
confidence: 99%
“…This research agenda is just beginning to be exploited in the trade and environment literature. Cherniwchan et al (2017) review and synthesize this work, using a framework that decomposes changes in sectoral emission intensities into changes in the composition of output across firms within a sector and changes in the composition of tasks within firms as well as actual changes in emission intensities at the task level.…”
Section: Effects Of Trade On the Environmentmentioning
confidence: 99%